Legal Responsibility of Buyers to Sellers Who Suffer Losses Due to Default in Online Sales and Purchase Agreements Based on Law No. 8 of 1999 Concerning Consumer Protection - Sinuhaji, Yefta Loviga; Anggusti, Martono; Gultom , Meli Hertati (PT FORMOSA CENDEKIA GLOBAL, 2025)
Online buying and selling is the process of buying and selling goods or services transactions carried out through electronic media, especially using the internet network, without a direct meeting between the seller and the buyer. This study aims to analyze the form of buyer default in online buying and selling transactions and examine the legal responsibility of buyers towards sellers who suffer losses, based on the provisions of Law Number 8 of 1999 concerning Consumer Protection and the Civil Code. To examine the application of legal norms in judicial practice through case studies, and to contribute to the development of civil law, especially in terms of justice, legal certainty, and balance of protection between sellers and buyers in electronic transactions. The method of collecting data is carried out through library research. Researchers collect legal data from books, articles, journals, documents, and other scientific sources. The research results show that buyers are legally responsible for losses suffered by sellers due to their default. The 1999 Law on Consumer Protection provides a strong legal basis for enforcing buyers' legal liability against sellers who suffer losses due to their default.